A Brief Analysis of the English-Chinese Subtitling Translation Strategies in Green Book from the Perspective of Culture - Liangqiu Lyu; Dexuan Chang (Journal of Linguistics and Communication Studies, 2023)
As a modern artistic form, film plays an important role in the cultural exchange between China and foreign countries. Subtitling translation is one of the most frequently used devices in film translation. The accuracy and rationality of subtitling translation are essential to cultural comprehension and exchange because of the big differences between English and Chinese. In the process of translating, culture is an important factor to be considered. This paper analyzes the features of subtitling translation, explores the influence of cultural differences on subtitling translation of the films, and demonstrates the subtitling translation strategies applied in the film Green Book. The paper aims to give some suggestions about subtitling translation of the films and further promote the exchange of different cultures.